Georg Rollenhagen an Michael Mästlin über sein Interesse an der Astrologia judiciaria: ein bisher unbekannter Brief vom 29. Dezember 1585 - Kühlmann, Wilhelm (Daphnis, 2025)
Abstract This essay provides an edition, translation, and commentary of a previously unpublished letter written by the renowned author and rector of Magdeburg, Georg Rollenhagen (1542-1609), to Michael Mästlin (1550-1631), who taught mathematics and astronomy in Tübingen. Rollenhagen gives information about his personal preferences for prognostic astrology, his models, plans and the common theological enemies of Mästlin.
Gesehen am 30.07.2025
Keywords: Brief; Maestlin, Michael; Rollenhagen, Georg